1985
DOI: 10.1111/j.1545-5300.1985.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

A Factor Analysis of Self‐Report Measures of Family Functioning

Abstract: Four well-known, self-report measures of family functioning were serially examined in order to identify a limited set of reliable concepts for describing families. Following the completion of four separate data collection procedures, a 75-item scale comprising 15 dimensions of family functioning was constructed. The dimensions appear reasonably independent of each other and have satisfactory psychometric properties. An initial effort to validate the scales was undertaken by contrasting scale scores obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
299
1
7

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(312 citation statements)
references
References 20 publications
5
299
1
7
Order By: Relevance
“…Consistent with prior research (Brown et al, 1997;DiClemente and Ponton, 1993;Donenberg et al, 2001Donenberg et al, , 2002, teens in this study reported high rates of risky sexual behavior; 39% reported ever having vaginal, anal, and/or oral sex, and among sexually active youths (n = 77), 42% had sex with a high-risk partner, 49% had sex while using drugs/alcohol, 66% had sex without Bloom, 1985) is a compendium of scales derived from other measures of family behavior. We used the five-item Family Disengagement Scale to measure the degree to which family members are involved in each others' lives (α = .50).…”
Section: Participantssupporting
confidence: 76%
See 2 more Smart Citations
“…Consistent with prior research (Brown et al, 1997;DiClemente and Ponton, 1993;Donenberg et al, 2001Donenberg et al, , 2002, teens in this study reported high rates of risky sexual behavior; 39% reported ever having vaginal, anal, and/or oral sex, and among sexually active youths (n = 77), 42% had sex with a high-risk partner, 49% had sex while using drugs/alcohol, 66% had sex without Bloom, 1985) is a compendium of scales derived from other measures of family behavior. We used the five-item Family Disengagement Scale to measure the degree to which family members are involved in each others' lives (α = .50).…”
Section: Participantssupporting
confidence: 76%
“…Parental symptom ratings on the Child Behavior Checklist (CBCL) (Achenbach, 1991a) were relatively consistent with diagnostic rates generated from the C-DISC; 50% and 49% of parents reported adolescent internalizing and externalizing symptoms in the clinical range. Rates of DISC-generated diagnoses in this sample are similar to those of other studies of general clinic populations (Jensen and Weisz, 2002).Consistent with prior research (Brown et al, 1997;DiClemente and Ponton, 1993;Donenberg et al, 2001Donenberg et al, , 2002, teens in this study reported high rates of risky sexual behavior; 39% reported ever having vaginal, anal, and/or oral sex, and among sexually active youths (n = 77), 42% had sex with a high-risk partner, 49% had sex while using drugs/alcohol, 66% had sex without Bloom, 1985) is a compendium of scales derived from other measures of family behavior. We used the five-item Family Disengagement Scale to measure the degree to which family members are involved in each others' lives (α = .50).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The subscale consists of five items, which are rated on a 5-point scale ranging from strongly disagree to strongly agree. The Family Cohesion subscale was developed based on a factor analysis of widely used family environment scales (Bloom, 1985). A sample item is: ''There is a feeling of togetherness in our family.''…”
Section: Perception Of Social Support From Friends (Pss-fr;mentioning
confidence: 99%
“…This scale was developed and prepared by Bloom et al (Bloom, 1985). In 1985 to evaluate the function of the system within the family.…”
Section: Family Functioning Questionnairementioning
confidence: 99%